Pembuatan Video Promosi Wisata Teras Alam Ulin Dengan Menggunakan Teknik Editing (Match Cut) - Stephanie Armonika Putri; Agusdi Syafrizal; Subhan Hartanto (JURNAL VOKASI TEKNIK, 2026)
In the making of the short film entitled "Kesalahan dalam Penyesalan" aims to explore the use of shooting techniques in cinematography. In the short film, it tells the story of a student who is careless and irresponsible in his academy in order to play games. Through this film, the author applies various types of shooting, such as extreme long shot, medium shot, close-up, cut-in, medium close-up, medium long shot, extreme close-up, wide shot, over shoulder shot. To highlight the expression and atmosphere in the story. Using the Multimedia Development Live Cycle (MDLC) method, the development of this short film consists of 6 stages: concept, design, material collection, manufacturing, testing, and distribution. The test of this film was through a questionnaire with a total of 40 respondents. And it was watched as many as 2,500, liked as many as 480, commented 66 and subscribed 100.